Extraction of Bioactive Compounds from Nepeta (Nepeta binaludensis Jamzad) by Novel Technologies - Mahalleh, Afsaneh Azimi; Mortazavi, Seyed Ali; Sharayei, Parvin; Azarpazhooh, Elham; Niazmand, Razieh (Asian Journal of Biological and Life Sciences, 2017)
Expanded snack was prepared from whole oleaster powder (WOP) and navy bean powder (NBP). Design expert was used to investigate the effects of extrusion conditions including feed moisture content (15- 25%), screw rate (150- 250 rpm), and different levels of WOP: NBP (20: 50, 50:50, and 65:35 %) on water activity (aw), water absorption index (WAI), water solubility index (WSI), oil absorption index (OAI) of expanded product. Results showed that increasing oleaster content caused an increase in the WAI, WSI, aw and soluble dietary fiber and a decrease in insoluble dietary fiber and OAI of the snacks. Optimum condition was found to be the blends of WOP/ NBP (20:80), screw rate of 200 rpm, and feed moisture content of 20% with 85.1% desirability. The extrusion process led to flours with high water and oil absorption, low water solubility and with potential for application in bakery, gluten free products.
Keywords: Nepeta binaludensis; Phenolic compounds; Pulse electric field; Ultrasound